A review: Partial discharge sensor applications and classification technique in high voltage cable - Auni W.N.; Rohani M.N.K.H.; Roslee N.F.; Rosmi A.S.; Kamaro M.; Mohd Aizam T.; Jalil M.A.A. (Institute of Advanced Scientific Research, Inc., 2023)
Partial discharge (PD)can cause a failure at high voltage (HV) equipment. Internal discharge, surface discharge and corona discharge can be identified as PD types which can lead to HV system failure. Power cable is one of the major applications in transmission line and power distribution. Therefore, early detection of PD at power cable is important due to prevent any sign of failure. In this paper reviews on how the PD present in power cable and some methods of PD detection at HV equipment. This review highlight on some application of AE sensor and electrical sensor in power cable. Since the PD signals are hard to differentiate due to noise surrounding during experiment, de-noising techniques are proposed in order to remove unwanted PD signal. Next, three popular techniques like Adaptive Neuro-Fuzzy Inference system (ANFIS), Artificial Neural Network (ANN) and Support Vector Machine (SVM) are review in the section of classification of PD signal. Feature extraction act as input of PD classification also introduced to reduce the size of PD data. 2020, Institute of Advanced Scientific Research, Inc. All rights reserved.